2018
DOI: 10.4103/ejd.ejd_351_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resterilization and storage time on sterility of paper/plastic pouches

Abstract: Objectives:Paper/plastic pouches are widely used packaging materials for autoclaving medical and dental equipment. Although these pouches are recommended for single use, they are generally reused in Thailand. This study aimed to determine the ability of paper/plastic pouches to maintain sterility after multiple sterilization processes and stored in a closed environment for up to 6 months.Materials and Methods:A total of 6720 paper/plastic pouches were divided into four experimental groups: new pouches, 1 time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…We found positive microbial growth in a positive control group at about 2 weeks' time in culture. This is different from the previous study that found positive growth within 8 days of culture with most samples showing positive results within 24 h [17]. This could be because in the current study the damage to the pouch was less than that in a previous study where there were many holes in a single pouch.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found positive microbial growth in a positive control group at about 2 weeks' time in culture. This is different from the previous study that found positive growth within 8 days of culture with most samples showing positive results within 24 h [17]. This could be because in the current study the damage to the pouch was less than that in a previous study where there were many holes in a single pouch.…”
Section: Discussioncontrasting
confidence: 99%
“…Our previous study found the intact barrier integrity of paper/plastic sterilization pouches after repeated sterilization in an ideal condition where the sterilization processes were repeated immediately (up to 6 times) with minimal handling and without real use in a clinic [17]. However, sterility maintenance of a pouch with 'resterilization' does not also mean sterility maintenance with 'reuse.'…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present work are in line with recent investigations presented by Puangsa-Ard et al 19 and Klumdeth et al. 23 In both studies, no microbial contamination was found in either the twice-used or the once-used pouches, and all remained sterile for up to 6 months.…”
Section: Discussionsupporting
confidence: 93%
“…One of the complications related to reusing these plastics is that they are marked as single-use by manufacturers. 19 In the impossibility of replacing plastic with other materials because of its many assets, this study aims to question the safety and efficacy of reusing sterilization pouches without compromising their sterilization conditions. 20,21 Therefore, the question and hypothesis raised are: Can sterilization pouches be used a second time while maintaining their sterilization conditions?…”
Section: Introductionmentioning
confidence: 99%